Risk prediction of major adverse cardiac events by high sensitivity troponin is modified by comorbidities. (14th October 2021) - Cohen, S; Mahler, S; Christenson, R; Allen, B; ,
Abstract: Background: High-sensitivity cardiac troponin (hs-cTn) is a well-established biomarker for the evaluation of Emergency Department (ED) patients with possible acute coronary syndrome. These patients often have comorbid conditions that may impact hs-cTn values. However, prior studies and current guidelines addressing the relationship between comorbidities and hs-cTn are limited. Purpose: To determine whether an interaction exists between comorbidities and baseline hsTnT values on the risk of 30-day major adverse cardiac events (MACE) in a multicenter United States (US) cohort. Methods: Adult ED patients with suspected acute coronary syndrome were prospectively enrolled in a multicenter cohort study in the US. Baseline blood samples were collected and hs-cTnT concentrations were measured at a central laboratory. Comorbid conditions, such as obesity, hypertension, hyperlipidemia, diabetes, coronary artery disease, congestive heart failure, renal disease, peripheral vascular disease, prior stroke, and history of coronary interventions, were collected at time of enrollment. The primary outcome was adjudicated MACE, defined as occurrence of myocardial infarction, cardiovascular or uncertain death, or coronary revascularization within 30 days. Hs-cTnT values were dichotomized using manufacturer's limit of quantification (LOQ) at 6 ng/dL and the upper reference limit (URL) of 19 ng/dL. The utility the LOQ and URL cut-offs in predicting MACE was evaluated using logistic regression. Effect modification of comorbid conditions was independently evaluated by including an interaction term between comorbidity and hs-cTnT. Results: Among 1460 participants with a baseline hs-cTn measurement, 46.3% (676/1460) were female and 37.1% (542/1460) were Black with a mean age of 57.6±12.9 years. The prevalence of MACE was 14.4% (210/1460). Participants with a baseline hs-cTnT below LOQ were 0.08 (95% CI: 0.04–0.16) times less likely to have MACE compared to those exceeding LOQ. Those with a baseline hs-cTnT exceeding URL were 9.5 (95% CI: 7.0–12.9) times more likely to have MACE. The presence of prior stroke significantly modified the association between baseline hs-cTnT below LOQ and risk of MACE (p=0.006). Among those with prior stroke (n=158), there was no significant association between baseline hs-cTnT below LOQ and risk of MACE (p=0.451). For the association between hs-cTnT above URL and MACE, significant negative interaction was detected by hypertension (p<0.001), hyperlipidemia (p=0.002), coronary artery disease (p=0.002), percutaneous coronary intervention (p=0.001), and congestive heart failure (p=0.038) comorbidity. Conclusion: In a diverse, multicenter, US cohort the association between baseline hs-cTnT and the risk of MACE was weakened by the presence of several comorbid conditions. This suggests that the safety of previously validated hs-cTnT diagnostic strategies may be diminished when applied to populations with a high prevalence of comorbid conditions. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Roche Diagnostics